ANALISIS POTENSI PAJAK SARANG BURUNG WALET DAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN (MBLB) PADA PENDAPATAN ASLI DAERAH (PAD) DI KOTA BITUNG - Dini Deviana Janet Suatan; Selly Mumu; Ratna Taliupan (LPPM Sekolah Tinggi Ilmu Ekonomi Petra Bitung, 2026)
This study aims to analyze the potential of Swiftlet Nest Tax and Non-Metallic Minerals and Rocks Tax (MBLB), measure the tax gap, and analyze the growth trend of tax revenues toward Regional Original Revenue (PAD) in Bitung City during 2021–2025. The research employed a descriptive quantitative method using secondary data obtained from the Regional Revenue Agency (BAPENDA) of Bitung City. The analytical techniques used were tax potential analysis, tax gap analysis, and trend analysis. The results indicate that the average potential of Swiftlet Nest Tax reached Rp74.424.000 with an average realization of Rp10.025,000 and an average tax gap of 86%. Meanwhile, the average potential of Non-Metallic Minerals and Rocks Tax (MBLB) reached Rp257,582,491 with an average realization of Rp85.784.400 and an average tax gap of 66.28%. Trend analysis showed that revenues from both taxes fluctuated during the study period. The study concludes that both taxes have significant potential to increase Regional Original Revenue (PAD), but their potential has not been fully optimized